Potential immunomodulatory role of sesamin in combating immune dysregulation associated with COVID-19 - Majdalawieh, Amin (2021)
The ongoing outbreak of novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused an unprecedented global health crisis. Development of a cure for this devastating disease is currently at full speed, with several vaccines against COVID-19 already authorized and administered. Currently, demand for these vaccines far exceeds supply. As such, boosting immunity represents a viable route to halt the rapid spread of SARS-CoV-2 and limit fatalities until vaccines become more readily and widely available. The use of phytochemicals appears to be a promising panacea. Sesamin, a lignan isolated from Sesamum indicum seeds, is known for its potent pharmacological properties, and is therefore hypothesized as a potential candidate in the therapeutic regimen against COVID-19. Herein, we highlight the confirmed therapeutic anti-inflammatory and immune-modulatory potential of sesamin against myriads of respiratory disorders, and tentatively suggest that sesamin may exert similar potent effects against COVID-19. Precisely, we speculate that sesamin may help alleviate COVID-19 via restoring Th1/Th2 balance and preventing inflammation and cytokine storm development. Additionally, we further support the promising role of sesamin against COVID-19 by underscoring the direct evidence, which suggests that sesamin may demonstrate promising inhibitory potential against three important SARS-CoV-2 targets, namely main protease, spike protein, and angiotensin-converting enzyme 2 receptor. Although preliminary, there is ample evidence to propose sesamin as a potential phytotherapeutic and prophylactic candidate against COVID-19. Further in vitro, in vivo, and preclinical studies are required to further substantiate the role of sesamin in the prevention and/or treatment of COVID-19.